Front desk - Yang, Kelly (New York : Arthur A. Levine Books/Scholastic Inc., 2018)
Recent immigrants from China and desperate for work and money, ten-year-old Mia Tang's parents take a job managing a rundown motel in Southern California, even though the owner, Mr. Yao is a nasty skinflint who exploits them; while her mother (who was an engineer in China) does the cleaning, Mia works the front desk and tries to cope with demanding customers and other recent immigrants--not to mention being only one of two Chinese in her fifth grade class, the other being Mr. Yao's son, Jason.
School Library Journal starred, March 2018
Booklist starred, April 2018
Bulletin of the Center for Children's Books starre, May 2018
Kirkus Starred, March 2018
Includes bibliographical references.
4.5.
Keywords: Immigrants -- Juvenile fiction; Chinese Americans -- Juvenile fiction; Self-confidence -- Juvenile fiction; Friendship -- Juvenile fiction; California, Southern -- Juvenile fiction; Immigrants -- Fiction; Chinese Americans -- Fiction; Hotels, motels, etc. -- Fiction; Self-confidence -- Fiction; Friendship -- Fiction; California, Southern -- Fiction